2017
DOI: 10.1109/tlt.2017.2708097
|View full text |Cite
|
Sign up to set email alerts
|

In-App Reflection Guidance: Lessons Learned Across Four Field Trials at the Workplace

Abstract: This paper presents a concept for in-app reflection guidance and its evaluation in four work-related field trials. By synthesizing across four field trials, we can show that computer-based reflection guidance can function in the workplace, in the sense of being accepted as technology, being perceived as useful and leading to reflective learning. This is encouraging for all endeavours aiming to transfer existing knowledge on reflection supportive technology from educational settings to the workplace. However, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…One avenue for supporting this data-collection could be the design of reflection prompts [14], attached to the elements of the representation as a qualitative support to increase the decision basis for the DDBM design team. Asking questions on business model design was researched as an evaluation approach for business models [17].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…One avenue for supporting this data-collection could be the design of reflection prompts [14], attached to the elements of the representation as a qualitative support to increase the decision basis for the DDBM design team. Asking questions on business model design was researched as an evaluation approach for business models [17].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…This could be explained by the following two facts. First, it is easier to describe (low-level reflection) or interpret an experience (medium level reflection) than to derive insights from reflection and put them in writing (high level reflection) [9]. Second, the experimental study (about 2 hours) may have been too far outside participant's real search practice for them to be able to derive deeper insights search behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Pammer et al [17] have shown that reflection on time log data incited users to generate insights about time management, and experiment with different time management strategies. Prior research has also shown that automatic reflection prompts can support reflective learning based on data: Fessl et al [9] implemented and evaluated reflection prompts that were embedded both directly within action, and with a larger temporal separation from action in informal and workplace learning contexts. The authors' reflection prompts reminded users to reflect, and pointed out salient data to users.…”
Section: Related Workmentioning
confidence: 99%
“…In cognitive psychology, data from large scale evaluation can now be used to validate models derived from the cognitive psychology that are commonly only studied in the laboratory, such as how concepts are formed in self-directed learning (Seitlinger et al, 2020). For intelligent systems, some general implications have been derived in terms of what models are involved (e.g., knowledge base, learner model, adaptation model), how they can be formalized and applied, e.g., by providing adaptive prompts for reflection (Fessl et al, 2017).…”
Section: Interdisciplinaritymentioning
confidence: 99%